1996
DOI: 10.2307/2967146
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Alcohol Drinking Among African American Adolescents: Implications for Violence Prevention

Abstract: This study sought to investigate the factors that predict alcohol drinking among African-American children of alcoholics (COA). The instruments used were: (1) the Children of Alcoholics Screening Test (J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…Frequent and heavy use of alcohol has been related to several negative social, mental, and physical health outcomes, such as increased violent behavior (Rodney, Mupier, & Crafter, 1996), criminal offenses (Greenfield, 1998), legal problems (Caetano, 1997; Herd, 1997b; Jones-Webb, Hsiao, Hannan, & Caetano, 1997b), family and interpersonal problems (Caetano, 1997; Jones-Webb et al, 1997b; Mulia et al, 2009), and alcohol-related injuries and illness (Greenfield, 2001; Jones-Webb, 1998; Yoon et al, 2001). Moreover, higher average volumes of alcohol consumption are associated with increased risk for the following major chronic diseases: mouth and oropharyngeal cancer, oesophageal cancer, liver cancer, breast cancer, unipolar major depression, epilepsy, alcohol use disorders, hypertensive disease, hemorrhagic stroke, and cirrhosis of the liver (Rhem et al, 2003).…”
Section: Greater Negative Consequences Related To Alcohol Use Among Amentioning
confidence: 99%
“…Frequent and heavy use of alcohol has been related to several negative social, mental, and physical health outcomes, such as increased violent behavior (Rodney, Mupier, & Crafter, 1996), criminal offenses (Greenfield, 1998), legal problems (Caetano, 1997; Herd, 1997b; Jones-Webb, Hsiao, Hannan, & Caetano, 1997b), family and interpersonal problems (Caetano, 1997; Jones-Webb et al, 1997b; Mulia et al, 2009), and alcohol-related injuries and illness (Greenfield, 2001; Jones-Webb, 1998; Yoon et al, 2001). Moreover, higher average volumes of alcohol consumption are associated with increased risk for the following major chronic diseases: mouth and oropharyngeal cancer, oesophageal cancer, liver cancer, breast cancer, unipolar major depression, epilepsy, alcohol use disorders, hypertensive disease, hemorrhagic stroke, and cirrhosis of the liver (Rhem et al, 2003).…”
Section: Greater Negative Consequences Related To Alcohol Use Among Amentioning
confidence: 99%
“…For instance, for every ounce of alcohol consumed, African-American youth have increasingly more social and academic problems when compared to White youth (Barnes & Welte, 1986). Alcohol use among African-American adolescents is also associated with low self-esteem and depression (Maag & Irvin, 2005); poor social and interpersonal skills (Hare & Hare, 1986); violence (Rodney, Mupier, & Crafter, 1996); and, is a precursor to most criminal offenses committed by African-American youth (Dawkins & Dawkins, 1983). Among African adolescents ages 12 to 20, alcohol is a primary contributor to the leading causes of death (e.g., unintentional accidents, suicide) (CDC, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…Research has not necessarily linked parents to these phenomena but has found that Black youth have comparable or even higher self-esteem than Whites and indicate a lower need for peer approval than Whites (Cernkovich & Giordano, 1992;Hughes & Demo, 1989). Low self-esteem and peer pressure have been repeatedly linked to substance use (Rodney, Mupier, & Crafter, 1996). Furthermore, researchers have found that the effect of friend's drug use is a stronger influence for Whites than for Blacks (Barnes, Farrell, & Banerjee, 1994).…”
Section: Literature Reviewmentioning
confidence: 99%